Spotlight on faculty member: Dr. Natanamurugaraj Govindan, marine bologist - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
Dr. Natanamurugaraj Govindan was born in August 1, 1979 at Pudukkottai district, Tamil Nadu State, India, where his parents and sister continue to play a big part in his life and career. He received his B.Sc. and M.Sc. degrees in Botany from Bharathidasan University, Trichyrappalli and B.Ed. degree in Biological Science from Alagappa University, Ka raikudi, India. Following his Ph.D specialization in Marine Algal Biotechnology from Bharathidasan University, India, Dr. Natanam was appointed Post-Doctoral Research fellow in the School of Engineering and Advanced Technology, Massey University, Palmerston North, New Zealand. He has written a book entitled "Marine diatoms from Ka raikal coastal region (India)': This book describes taxonomy and identification of marine microalgae (particularly diatoms) for biotechnology students.